The combined effect of neonatal hypothyroidism and low family income on intellectual disability: A review of mechanisms and interventions - Sutanti, Sutanti; Suryawan, I Wayan Bikin (Jurnal Prima Medika Sains, 2025)
This review investigates the combined effect of neonatal hypothyroidism and low family income on the prevalence of intellectual disability, drawing insights from existing literature, including specific findings from studies involving neonatal cases such as 15 cases at Wangaya Regional Hospital Denpasar. Neonatal hypothyroidism significantly impacts cognitive development due to the critical role of thyroid hormones in brain maturation. Concurrently, low family income acts as a risk factor for intellectual disability by limiting access to essential healthcare, education, and developmental resources. The review explores the epidemiology of neonatal hypothyroidism, highlighting global and regional variations influenced by genetic, environmental, and socioeconomic factors. It delves into the mechanisms by which neonatal hypothyroidism affects brain and cognitive function, leading to deficits in intelligence, memory, attention, and executive function. Furthermore, the review examines the relationship between socioeconomic status and intellectual disability, emphasizing the role of resource scarcity and environmental factors associated with poverty. Findings from the reviewed literature suggest a compounding effect of neonatal hypothyroidism and low family income on a child's cognitive development and intellectual disability risk. Addressing this complex interplay necessitates a multifaceted approach, including early detection, prompt treatment, and integrated interventions spanning healthcare, education, and social support services. The review underscores the importance of equitable access to newborn screening, comprehensive early intervention programs, and family-centered support for children from low-income households.